Reproductive science and integrated conservation - Holt, W. V. (Conservation biology series (Cambridge, England) ;, 2003)
Reproductive systems vary widely between species. This book reviews the many factors that influence reproduction, including genetics, behaviour and nutrition in a diverse range of animals. Leading authorities assess the potential relevance of the recent rapid advances in reproductive technology and medicine to the management and conservation of wildlife species.